Hubungan berat tas dengan gangguan muskuloskeletal pada siswa SMAN 4 Denpasar, Bali-Indonesia - I Putu Putrayasa Wiguna; I Putu Gede Adiatmika (DiscoverSys Inc., 2019)
Introduction: Several major subjects contained in the current curriculum in high school that make students must bring a lot of book. This causes the bag used by high school students become heavier, which can cause musculoskeletal disorders in high school. This research aims to find the relationship between the weight of bags used to school with musculoskeletal disorders in high school students.Method: This research is an analytic cross-sectional design of the high school students from October to December 2015. The level of musculoskeletal disorders was obtained using a Nordic Body Map questionnaire. Pearson Correlation test used to find out the relationship between weight bag with musculoskeletal disorders.Result: The result was found that the weight of bags have a relationship with musculoskeletal disorders in high school students. Results of the analysis of 91 samples showed a p-value = 0.02, which means that there is a statistically significant relationship (p<0.05).Conclusion: Weight bag has a relationship with musculoskeletal disorders in high school students, where the increasing weight bag will affect the severity of musculoskeletal disorders that appear on the subject.